Preparation of an antibacterial gel from the pulp of Aloe vera (Aloe vera). - García Rodriguez, Sarai; Ramírez Hernández, Johana; Bárcena Vicuña, Guadalupe Gabriela; Reyes Jurado, D Fátima (Revista Productos Naturales, 2022)
This project proposes the elaboration of an antibacterial gel from Aloe vera parenchyma (gel) with lavender and jasmine essence.